Mechanical Parameters Effects on Acoustic Absorption at Polymer Foam - Lyes Dib; Samia Bouhedja; Hamza Amrani (Advances in Materials Science and Engineering)
Polymer foams have acoustic absorption properties that play an important role in reducing noise level. When the skeleton is set to motion, it is necessary to use generalized Biot-Allard model which takes into account the deformation of the skeleton and the fluid and the interactions between them. The aim of this work is to study the quality of acoustic absorption in polyurethane foam and to show the importance of the structural vibration of this foam on the absorption by varying mechanical parameters (Young’s modulus E, Poisson’s coefficient ν, structural damping factor η, and the density ρ1). We calculated the absorption coefficient analytically using classical Biot formulation (us, uf) and numerically using Biot mixed formulation (us, p) in 3D COMSOL Multiphysics. The obtained results are compared together and show an excellent agreement. Afterwards, we studied the effect of varying each mechanical parameter independently on the absorption in interval of ±20%. The simulations show that these parameters have an influence on the sound absorption around the resonance frequency fr.